Temporal Trend of Severe Obesity in Brazilian State Capitals (2006–2021) - Flávia Santos Batista Dias; Tiago Feitosa da Silva; Yara de Moura Magalhães Lima; Luana Silva de Farias; Jhonatan Gomes Gadelha; Alanderson Alves Ramalho (Obesities, 2023)
The aim of this study was to analyze the trend of severe obesity in the capitals of the Brazilian states and the Federal District, from 2006 to 2021. For this purpose, a time-series, population-based, observational study was designed using data from the VIGITEL Survey. The dependent variable of this study was the prevalence of severe obesity, which was defined as a body mass index ≥ 40 kg/m2. Time series analysis was conducted using Joinpoint Regression Analysis Software v.4.9.1.0. In this study, a normal distribution was assumed, and the average annual percentage change (AAPC) and 95% confidence intervals (95% CIs) were presented. In total, 778,445 individuals participated in the study (38.2% were male and 61.8% were female). The prevalence of severe obesity has increased from 1.1% in 2006 to 1.9% in 2021. The average annual percentage change indicates an upward trend for the period (AAPC: 4.7; 95% CI: 3.8; 5.7). When stratifying the trend of severe obesity by sex, a significant upward trend was observed for females (AAPC: 4.3; 95% CI: 1.9; 6.8). There was a significant upward trend for all age groups, skin colors, and education levels. However, the older age groups and those with less education had lower AAPC.